Strengthening Farming Businesses in the Environmentally Friendly Agriculture Program in Calingcing Village, Tasikmalaya - Leny Yuliyani; Anita Dwy Fitria; Gilang Vaza Benatar; Indra Permana (Universitas Veteran Bangun Nusantara, 2025)
The community empowerment program that partners with KWT Dahlia was created to utilize underutilized local resources such as household waste, harvest residues, and clove plants that can be made into local microorganisms, organic fertilizers, and botanical pesticides to support environmentally friendly agriculture in Calingcing Village. This community empowerment uses the PRA (Participatory Rural Appraisal) approach. The basic principle of this approach is to fully involve the community in every stage of the activity with a focus on participation based on the principle of learning from the community, the active role of the community as the main subject, the exchange of knowledge and experience between community members, and the role of outsiders as facilitators. The results of the activity showed that there was an increase in the knowledge of KWT Dahlia members by 66.7% in the introduction of sustainable environmentally friendly agriculture, the practice of using PUTK and pH meters. While in the assistance to strengthen environmentally friendly farming, there was an increase in knowledge of 94.4%. The results of the activity evaluation showed that according to KWT Dahlia members, the material provided was beneficial. As many as 88.9% of KWT Dahlia members stated that this community empowerment activity was very beneficial. The level of ease of the material according to 83.3% of KWT Dahlia members is quite easy to understand. While the level of novelty of the material provided is 94.4% of respondents answered new things. And the most important thing is that 66.7% of KWT Dahlia members are very enthusiastic and 33.3% are enthusiastic about implementing the technology and innovation provided by the community service team. Keywords: Participatory Rural Appraisal, Eco-friendly farming, farming